A new role of Yb3+—an energy reservoir for lanthanide upconversion luminescence. Issue 22 (25th May 2021) - Xu, Li; Liu, Yu; Zhou, Ziwen; Sun, Xianhao; Ud Din, Isam; Khan, Fahim; Li, Yanzeng; Li, Hanyang; Ren, Jing; Carvajal, Joan J.; Zhang, Jianzhong; Liu, Lu
Abstract : We proposed a novel energy cycling mechanism by introducing Yb 3+  as an energy reservoir to improve the Ln 3+  upconversion intensity. The key of the energy cycling mechanism is suppressing the energy dissipation and/or facilitating the ESA population. Abstract : Thus far, Yb 3+ has usually served as a sensitizer to improve energy harvesting in lanthanide ion based luminescent materials. Herein, besides the well accepted character as a sensitizer, we revealed a new role of Yb 3+, namely an energy reservoir, to improve the upconversion efficiency of several lanthanide activators. The energy cycling between lanthanide activator A 3+ and energy reservoir Yb 3+ is mainly responsible for the improvement. This energy cycling can facilitate energy utilization by A 3+ for the generated upconversion luminescence. Specifically, this energy cycling not only alleviates the dissipation of energy produced at the intermediate level, needed to promote electrons to a higher energy level, but also provides an additional excited-state absorption route for A 3+ . The benefits of the proposed Yb 3+ energy reservoir as well as the energy cycling mechanisms were verified using three representative activators, Nd 3+, Tm 3+, and Er 3+ . This study can open new possible avenues to exploit Yb 3+ and enrich the available upconversion luminescence pathways of lanthanide ions.